The role of Islamic religious education teacher in increasing student discipline: A case study at SMP Negeri 2 Polokarto Sukoharjo - Pangestu, Salvinia Iga; Abidin, Zaenal (Gema Wiralodra, 2023)
This research leads to the role of Islamic Religious Education (PAI) teachers in improving student discipline at SMP Negeri 2 Polokarto Sukoharjo. This study discusses the formulation of the problem (1) The role of Islamic Religious Education (PAI) teachers in increasing student discipline at SMP Negeri 2 Polokarto Sukoharjo, (2) Supporting and inhibiting factors in increasing student discipline at SMP Negeri 2 Polokarto Sukoharjo. This qualitative research uses a phenomenological approach with the object of Mr. Heriyanto as a teacher of Islamic Religious Education at school and one of the students at SMP Negeri 2 Polokarto, which helps obtain more detailed information. The data acquired shows that the inhibiting factors that cause student indiscipline at SMP Negeri 2 Polokarto are due to factors from family, peers, and the environment, which causes children to no longer be enthusiastic about doing things related to discipline. Thus the role of the PAI teacher in increasing student discipline at Polokarto 2 Public Middle School is that teacher must be able to guide students to become students who have mature thinking, are independent, and can solve their problems, the teacher must be able to be a role model for his students to carry out all activities in the school environment, and Finally, the teacher must be able to set a good example for his students both in terms of attitude, behavior, language.